Fluency and accuracy : toward balance in language teaching and learning - Hammerly, Hector (Multilingual matters (Series), 1991)
A text which provides solutions to the problem of inaccuracies resulting from an emphasis on fluency. It suggests that the restoration of balance depends upon a greater understanding of proficiency and of the roles of cross-linguistic influence, systematic instruction and the correction of errors.